DIFFERENTIAL DIAGENESIS OF STRONTIUM IN ARCHAEOLOGICAL HUMAN DENTAL TISSUES - Budd P.; Montgomery J.; Barreiro B.; Thomas R.G. (My University, 2000)
The investigation of prehistoric human migration from the measurement of Sr-isotope ratios within preserved tissue is critically dependent on the preservation of biogenic Sr. A number of recent studies have involved isotope ratio measurements on samples of archaeological tooth and bone, but doubt remains as to the extent of diagenesis in various skeletal tissues and the effectiveness of procedures designed to decontaminate them. The authors have compared Sr abundance and isotope ratios in enamel and dentine from archaeological teeth in order to assess the integrity of the biogenic Sr signal preserved within the respective tissues. It is concluded that enamel appears, in most cases, to be a reliable reservoir of biogenic Sr, but that dentine, and by implication bone, is not. The diagenesis of dentine is highly variable even between burials within a single site. For the majority of teeth, dentine diagenesis was not simply by addition of soil-derived Sr, but involved substantial, sometimes complete, turnover of the original biogenic material. It is suggested that, for most of the samples investigated, current decontamination techniques may not have been effective in isolating biogenic Sr from dentine. Similar considerations are likely to apply to archaeological and fossil bone, but the possibility arises to use dentine and enamel measurements to assess the effectiveness of decontamination procedures which may then be used for bone.